Colchicine in Managing Skin Conditions: A Systematic Review - Stefano Dastoli; Steven Paul Nisticò; Pietro Morrone; Cataldo Patruno; Antonio Leo; Rita Citraro; Luca Gallelli; Emilio Russo; Giovambattista De Sarro; Luigi Bennardo (MDPI AG, 2022)
(1) Background: Colchicine is a natural alkaloid with anti-inflammatory properties used to treat various disorders, including some skin diseases. This paper aims to incorporate all the available studies proposing colchicine as a treatment alternative in the management of cutaneous conditions. (2) Methods: In this systematic review, the available articles present in various databases (PubMed, Scopus-Embase, and Web of Science), proposing colchicine as a treatment for cutaneous pathological conditions, have been selected. Exclusion criteria included a non-English language and non-human studies. (3) Results: Ninety-six studies were included. Most of them were case reports and case series studies describing colchicine as single therapy, or in combination with other drugs. Hidradenitis suppurativa, pyoderma gangrenosum, erythema nodosum, erythema induratum, storage diseases, perforating dermatosis, bullous diseases, psoriasis, vasculitis, acne, urticaria, stomatitis, actinic keratosis, and pustular dermatosis were the main diseases discussed in literature. Although the therapeutic outcomes were variable, most of the studies reported, on average, good clinical results (4) Conclusions: Colchicine could be, as a single therapy or in combination with other drugs, a possible treatment to manage several skin diseases.